Signal processing, perceptual coding, and watermarking of digital audio [ advanced technologies and models - He, Xing (Gale virtual reference library, 2012)
"This book focuses on watermarking, in which data is marked with hidden ownership information, as a promising solution to copyright protection issues and deals with understanding human perception processes and including them in effective psychoacoustic models" -- Provided by publisher